Encapsulating Sn(OH)4 Nanoparticles in Micropores of Mesocarbon Microbeads: A New Anode Material for High‐Performance Lithium Ion Batteries. Issue 3 (4th February 2021) - Zhang, Bo; Zhou, Juncheng; Sun, Xiaoxuan; Luo, Birong; Li, Dejun; Gu, Xingxing; Zhao, Yang
Abstract: A novel Sn(OH)4 /mesocarbon microbeads (MCMB) anode material has been successfully prepared by skillfully encapsulating the Sn(OH)4 nanoparticles into the micropores of MCMB via a simple vapor deposition approach. The electrochemical results demonstrate that the Sn(OH)4 /MCMB anode exhibits a high reversible capacity of 904 mAh g −1 after 500 cycles at a current density of 100 mA g −1, which is far higher than that of the SnO2 /MCMB (501 mAh g −1 ) and Sn/MCMB (364 mAh g −1 ). Such transcendence can be attributed to the ultrasmall sizes of Sn(OH)4 nanoparticles and rapid lithium ions transport channels provided by micropores on the surface of MCMB. More importantly, the encapsulated Sn(OH)4 particles inside the micropores decrease the exposure to the electrolyte to ensure the formation of stable solid electrolyte interphase films as well as accommodating electrode expansion during charge–discharge, which is beneficial to achieve a stable cycling performance. Therefore, the unique nanostructures of Sn(OH)4 /MCMB ensure it becomes a novel promising anode material for the high‐performance lithium ion batteries. Abstract : Encapsulating ultra‐small Sn(OH)4 into the micropores of mesocarbon microbeads can decrease the exposure to the electrolyte, alleviate the electrode expansion, and thus contribute to excellent electrochemical performances.